2019
DOI: 10.1136/tobaccocontrol-2018-054718
|View full text |Cite
|
Sign up to set email alerts
|

Delphi study among international expert panel to develop waterpipe-specific health warning labels

Abstract: BackgroundWaterpipe (WP) smoking is increasing globally. The rise of WP has been fuelled by widespread misperception of reduced-harm compared to cigarettes. Health warning labels (HWLs) are one strategy to communicate smoking-related risks and address reduced-harm misperceptions. Therefore, the development of WP-specific HWLs represents a priority for WP control.MethodsA panel of experts in WP science developed 28 WP-specific HWLs corresponding to five themes (health risks, addiction, harm to others, WP-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Similar effects of warnings related to child health have been observed among cigarette smokers 29 . These findings are in accordance with a recent international expert panel consensus, where labels related to waterpipe’s harmful effects on newborn children were identified as being among the most effective at communicating WTS-related risks 30 . Furthermore, our results show that the motivation to quit in response to text warning labels was significantly higher among females than males for text warnings related to harm to children or during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Similar effects of warnings related to child health have been observed among cigarette smokers 29 . These findings are in accordance with a recent international expert panel consensus, where labels related to waterpipe’s harmful effects on newborn children were identified as being among the most effective at communicating WTS-related risks 30 . Furthermore, our results show that the motivation to quit in response to text warning labels was significantly higher among females than males for text warnings related to harm to children or during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…It is estimated that approximately 100 million people, particularly teenagers, use this kind of smoking 4 . Since the period 2009-2016, studies reporting on WPS indicated a 0.4% to 2.9% annual increase in current WPS in the Eastern Mediterranean and European Regions, and 0.3% to 1.0% increase in the USA [5][6][7] . Population data indicate that from 3.3% to 7.5% of US youths have tried waterpipe 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Some collaborative efforts between researchers from different Arab states addressed common health concerns, like smoking and viral infections. With smoking rates being among the highest worldwide in the Arab world, one study focused on health warning labels that are waterpipe-specific; researchers from Lebanon, Syria and Tunisia contributed in the process 37. Scientific evidence about the waterpipe's harmful effects and the importance of tobacco control were emphasised in the labelling strategies 37.…”
Section: Discussionmentioning
confidence: 99%